Serotonin transporter deficiency, but not absence of platelet serotonin, impairs thrombus formation in a model of deep vein thrombosis - Naber, Katharina; Mauler, Maximilian; Schanze, Nancy; Kröning, Pia; Stallmann, Daniela; Dürschmied, Daniel; Westermann, Dirk; Gauchel, Nadine (Research and practice in thrombosis and haemostasis, 2025)
Background - The majority of peripheral serotonin is stored in dense granules of circulating blood platelets and released upon platelet activation. Recently, an immunomodulatory role of serotonin in inflammation has been found, influencing the recruitment of leukocytes, especially neutrophils. - Objectives - Since deep vein thrombosis creates an inflammatory milieu, called thromboinflammation, this study examined the impact of peripheral platelet serotonin on the development of venous thrombosis. - Methods - To induce deep vein thrombosis, a stenosis model of the inferior vena cava was used. Six- to 8-week-old C57BL/6 (wild-type [WT]), selective serotonin reuptake inhibitor-treated C57BL/6 (depleted serotonin pools in platelets), serotonin transporter knockout (SERT-/-), and tryptophan hydroxylase 1 knockout (Tph1-/-) mice were used. Thrombus volume was measured, and its composition was analyzed after 48 hours using immunofluorescence microscopy. Neutrophils and platelet-neutrophil complexes were analyzed using flow cytometry. - Results - SERT-/- mice formed significantly fewer and smaller thrombi compared with WT (mean ± SD, 1.09 mm3 ± 2.53 vs 13.1 mm3 ± 11.1; P = .002) and Tph1-/- mice (1.09 mm3 ± 2.53 vs 11.3 mm3 ± 6.84; P = .02) and had lower levels of neutrophils in the blood. Thrombi in the WT and Tph1-/- groups were comparable. In SERT-/- mice, there was no decrease in circulating platelet-neutrophil complexes. - Conclusion - The extent of venous thrombosis did not depend on peripheral serotonin in our mouse model, but rather on the presence of the serotonin transporter. In the absence of the serotonin transporter, the thrombogenic property as well as the overall immune response to venous thrombosis was reduced. The distribution of the serotonin transporter on immune cells and its thrombogenic potential should be studied further.
Online verfügbar: 15. Juli 2025, Artikelversion: 6. August 2025
Gesehen am 11.11.2025